2023
DOI: 10.1002/gps.5911
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation, loneliness, and motoric cognitive risk syndrome among older adults in China: A longitudinal study

Abstract: Objectives This study aimed to investigate the associations between social isolation, loneliness, and motoric cognitive risk syndrome (MCR) among older adults in China. Methods Data were obtained from the China Health and Retirement Longitudinal Study in the 2011 and 2015 waves. Social isolation and loneliness were measured by an index and an item, and MCR was defined as subjective cognitive complaints and slow gait. Multivariable logistic regression analyses were performed to examine the associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…included 3125 participants from the 2011 and 2015 waves of the CHARLS 11 and did not find any significant association of social isolation with incident MCR in men (HR: 1.04, 95% CI: 0.80–1.36) or women (HR: 1.19, 95% CI: 0.90–1.59) after adjusting for confounding factors. 11 However, since these two studies were both conducted in the same population (CHARLS participants), further studies are needed in other populations to validate these findings.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…included 3125 participants from the 2011 and 2015 waves of the CHARLS 11 and did not find any significant association of social isolation with incident MCR in men (HR: 1.04, 95% CI: 0.80–1.36) or women (HR: 1.19, 95% CI: 0.90–1.59) after adjusting for confounding factors. 11 However, since these two studies were both conducted in the same population (CHARLS participants), further studies are needed in other populations to validate these findings.…”
Section: Discussionmentioning
confidence: 86%
“…Although our study is the first to examine the relationship between social frailty and MCR in older adults, recent studies have investigated the relationships between several aspects of social frailty and MCR, including social support, social interactions, and social isolation. 10 , 11 , 12 , 13 Social support is one component of social frailty (i.e., lacking social resources), and previous studies have reported inconsistent results across different populations. 10 , 13 For example, Felix et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations